PROSTHESIS OF AORTIC VALVE BY STENTED AND STENTLESS BIOLOGICAL PROSTHESES: INTERMEDIATE ANALYSIS OF RESULTS - D. A. Astapov (Вестник хирургии имени И.И. Грекова, 2017)
OBJECTIVE. The authors assessed an impact of the design of biological prosthesis on efficacy of aortic valve replacement in elderly patients. MATERIAL AND METHODS. Randomized parallel controlled prospective study was carried out. The patients were divided into groups with stented and stentless prostheses. A value of peak valve gradient was determined as a primary end point. RESULTS. The peak gradients were significantly higher in the first group than in the second group. There was noted a significant difference in value of miocardial hypertrophy of the left ventricular (mass index of the myocardium) during 30-day terms after operation. CONCLUSIONS. The final results would be possible to consider after the end of the study. The results of intermediate analysis supported the validity of the proposed hypothesis.